PLS regression in the spectrophotometric data for the simultaneous determination of levodopa and carbidopa in pharmaceutical preparations by using an enzymatic stopped-flow FIA technique - Grunhut, Marcos (2007)
An enzymatic stopped-flow-injection analysis is proposed for simultaneous determination of levodopa and carbidopa in pharmaceutical preparations. The dopaquinones obtained after the oxidation catalized by the enzyme were measured by spectrophotometric method. A reduced calibration matrix based on a central composite experimental design was built and Partial Least Squares (PLS) was applied on the spectral data after reaction with the enzyme. The LOD was 0.015 and 0.0028 mg ml-1, respectively and the sample throughput was 22.5 h-1. The proposed method was applied to pharmaceutical preparations and the results are in close agreement with pharmacopeial method. The recovery study and results were satisfactory.